The MUC5B Promoter Polymorphism Associates With Severe COVID-19 in the European Population - van Moorsel, Coline H. M.; van der Vis, Joanne J.; Duckworth, Anna; Scotton, Chris J.; Benschop, Claudia; Ellinghaus, David; Ruven, Henk J. T.; Quanjel, Marian J. R.; Grutters, Jan C. (Frontiers in Medicine, 2021)
Diversity in response on exposure to severe acute respiratory syndrome coronavirus 2 may be related to the innate immune response in the elderly. The mucin MUC5B is an important component of the innate immune response and expression levels are associated with the MUC5B promoter polymorphism, rs35705950. The high expressing T-allele is a risk allele for the non-infectious aging lung disease idiopathic pulmonary fibrosis (IPF). Given the theory of trade-offs in aging lung disease and the importance of mucin expression for an adequate immune response, we hypothesized that the T-allele is protective against severe COVID-19 disease. Methods MUC5B rs35705950 was genotyped for 108 Dutch patients requiring hospitalisation for COVID-19. For replication, genotypes were obtained from the severe COVID-19 GWAS group from Italy (n=835) and Spain (n=775), and from the UK-Biobank (n= 436), each with respective control cohorts. Results The rs35705950 T-allele frequency was significantly lower in Dutch white patients (n=83) than in controls (0.04 vs 0.10; p=0.02). This was replicated in the Italian (0.10 vs 0.13; p=0.04), Spanish (0.10 vs 0.13; p=0.03), and UK (0.08 vs 0.11; p=0.001) case-control cohorts. Meta-analysis showed a negative association for the T-allele with COVID-19 disease (0.75 (CI: 0.67–0.85); p=6.63e-06). Conclusions The MUC5B rs35705950 risk allele for IPF is protective against development of severe COVID-19 disease, and a further example of trade-offs in aging lung diseases.